A review paper on the hazardous effect of plastic debris on marine biodiversity with some possible remedies - Hasnat, Md Abul; Rahman, Mohammad Atikur (Asian Journal of Medical and Biological Research, 2018)
The consequences of plastic debris in the marine environment were reviewed, and possible solutions were presented. The extent of marine plastic debris-related problems surpasses many other marine problems, as plastics may be transported globally and no unaffected areas seem to exist. Many animal species are in risk, most commonly studied are the effects on marine mammals and seabirds. Marine plastic debris creates new concerns such as entanglement, ghost fishing, and impaction of digestive tracts in animals. It also increases the severity of already existing concerns such as transport, exposure and uptake of organic pollution, with reduced fitness and impaired reproduction and increased mortality rates as consequences. To alleviate the problems, reducing the extent of marine plastic pollution is critical. Possible methods were identified as collecting and incentivizing recycling of marine plastic debris; redirecting production from petroleum plastics to biodegradable varieties; increase public awareness to reduce marine littering; stricter enforcement of current legislation as well as implementation of stricter legislation and harsher penalties for breaking it. Asian J. Med. Biol. Res. September 2018, 4(3): 233-241